Testing A Measurement Scale Of Organizational Commitment Using A Confirmatory Factor Analysis - Esmael M. A. Tabouli; Nasser Habtoor; Mohammad Nashief S. (Leena and Luna International, Chikusei, Japan, 2024)
The present study seeks to develop a conceptual framework for measuring organizational commitment among employees in banking institutions by adopting three appropriate dimensions of measurement: affective commitment, continuous commitment and normative commitment. To achieve this goal, we used a confirmatory factor analysis (CFA) through AMOS software. Based on the results, it was found that this model is a valid and reliable model that can be used for measuring organizational commitment among employees in banking institutions in Libya.